A case of Plasmodium falciparum malaria presenting 13 years after leaving an endemic area - David Hettle; Mustafa Elsayed; Samuel Mensah; Francesca Neuberger; Debbie Nolder; Hristina Vasileva; Kevin Tetteh; Tim Cutfield; Imogen Jones; Spencer Polley; Louise Turner; Thomas Lavstsen; et al. (Infectious Diseases, 2025)

Perspectives: The look insight – magnet resonance imaging (MRI) of the inner life of plants - Ljudmilla Borisjuk; Thomas Neuberger (Journal of Plant Physiology, 2025)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global brain signal in awake rats - Yuncong Ma; Zilu Ma; Zhifeng Liang; Thomas Neuberger; Nanyin Zhang (Brain Structure and Function, 2020)

Neurobiological effect of selective brain cooling after concussive injury - Alexa Walter; Katie Finelli; Xiaoxiao Bai; Brian Johnson; Thomas Neuberger; Peter Seidenberg; Timothy Bream; Mark Hallett; Semyon Slobounov (Brain Imaging and Behavior, 2018)

Localization of osteoblast inflammatory cytokines MCP-1 and VEGF to the matrix of the trabecula of the femur, a target area for metastatic breast cancer cell colonization - Karen M. Bussard; Noriaki Okita; Neil Sharkey; Thomas Neuberger; Andrew Webb; Andrea M. Mastro (Clinical & Experimental Metastasis, 2010)